2018
DOI: 10.1017/s000711451800154x
|View full text |Cite|
|
Sign up to set email alerts
|

The Japanese food score and risk of all-cause, CVD and cancer mortality: the Japan Collaborative Cohort Study

Abstract: Few studies have reported the association between the Japanese diet as food score and mortality. This study aimed to investigate adherence to the Japanese food score associated with all-cause, CVD and cancer mortality. A total of 58 767 (23 162 men and 34 232 women) Japanese participants aged 40-79 years, who enrolled in the Japan Collaborative Cohort Study between 1988 and 1990, were included. The Japanese food score was derived from the components of seven food groups (beans and bean products, fresh fishes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
61
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 32 publications
0
61
0
Order By: Relevance
“…The previous study had suggested that a dietary pattern with similar weights contributed to higher overall nutrient adequacy and lower oxidative stress [8]. Another study has also indicated that a Japanese food score that did not encourage rice intake was related to lower cardiovascular disease mortality [1]. These findings suggest that, although rice is a staple food in Japan, a diet that includes excessive and single intake of rice may not be desirable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous study had suggested that a dietary pattern with similar weights contributed to higher overall nutrient adequacy and lower oxidative stress [8]. Another study has also indicated that a Japanese food score that did not encourage rice intake was related to lower cardiovascular disease mortality [1]. These findings suggest that, although rice is a staple food in Japan, a diet that includes excessive and single intake of rice may not be desirable.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that a traditional Japanese diet is associated with a lower risk of mortality [1][2][3] and adverse health outcomes (e.g. disability, dementia, depression) [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…However, diets in other regions are different from those in Western countries, and it is not practical to recommend Western dietary patterns to other regions, e.g., Asian countries. Recently, the Japan Collaborative Cohort study that evaluated the effect of high Japanese food scores (i.e., high of consumption of rice, miso soup, seaweeds, pickles, green and yellow vegetables, fish, and green tea, and low consumption of beef, pork, and coffee) found that adherence to a Japanese food score may have benefits for CVD prevention [74]. However, more evidence is needed to confirm the benefits of Japanese food and other Asian dietary patterns on CVD prevention.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the Japanese diet (JD) has drawn attention as a distinct diet. In order to evaluate the habitual Japanese diet intake, JD scores have been used as a major approach in nutritional epidemiology research (13,14). The JD score is an index indicating that food groups such as vegetables, fruits, fish, and E-mail: seurat@asu.aasa.ac.jp pickles, are characterized by JD patterns.…”
mentioning
confidence: 99%
“…The JD score is an index indicating that food groups such as vegetables, fruits, fish, and E-mail: seurat@asu.aasa.ac.jp pickles, are characterized by JD patterns. Recent studies indicate that higher JD scores prevent chronic diseases, such as cancer and cardiovascular disorders (13). Moreover, the intake of individual food groups, including vegetables and fruits, is associated with a lower risk of type 2 diabetes (15).…”
mentioning
confidence: 99%